A Radiographic Study of Biomechanical Relationship between the Achilles Tendon and Plantar Fascia. - Zhu, Genrui; Wang, Zhifeng; Yuan, Chengjie; Geng, Xiang; Zhang, Chao; Huang, Jiazhang; Wang, Xu; Ma, Xin (BioMed Research International, 2020)
Background. Previously, scholars have concluded that the Achilles tendon and the plantar fascia were closely biomechanically related, although there is little clinical evidence of the relationship between the two. To investigate the biomechanical relationship between the Achilles tendon and the plantar fascia, the author used standing lateral ankle radiographs of patients with insertional Achilles tendonitis to determine the biomechanical relationship between the Achilles tendon and plantar fascia. Methods. The author collected standing lateral ankle radiographs from patients with insertional Achilles tendonitis who accepted surgical treatment in the author's hospital from March 2009 to July 2018. According to whether there were bone spurs on the posterior side of the calcaneus, patients were divided into group A (spur present on the posterior side) and group B (spur not present on the posterior side). The positive rates of spurs on the plantar side of the calcaneus were determined in group A and group B. The chi-square test was used to compare the measurement results between the two groups. Results. In group A, 13 heels were positive for calcaneal bone spurs, and the positive rate was 65.0%. In group B, 3 heels were positive for plantar calcaneal spurs, and the positive rate was 12%. Among all 16 patients with positive plantar calcaneal spurs, 13 had posterior calcaneal spurs (accounting for 81.3%), and 3 had negative results, accounting for 18.7%. There was a significant difference between the results in groups A and B (P < 0.05). Conclusion. There is a relationship between posterior calcaneal spurs and plantar calcaneal spurs in patients with insertional Achilles tendonitis, which can be inferred as resulting from the increasing tension in the biomechanically complex relationship between the Achilles tendon and the plantar fascia.